MODEL PEMBANGUNAN EKONOMI DESA BERBASIS AGRO EKOWISATA SEBAGAI PENYANGGA EKONOMI KAWASAN TAMAN NASIONAL BROMO TENGGER SEMERU: STUDI PADA DESA NGADAS KECAMATAN PONCOKUSUMO KABUPATEN MALANG - Fajar Supanto (UPT Penerbitan Universitas Jember)
In supporting the economic development of the tourism sector, Malang Regency Government in 2007 set Ngadas village as a tourist village. But so far has not appeared stretching economy as a result of the determination of that status. Poverty remains a problem that must be addressed. This study aims to formulate and develop a regional economic development model based on agro-ecotourism as an economic buffer area of Bromo Tengger Semeru National Park, as well as implementing the model in Ngadas Tourism Village. The research was conducted within a period of two years with a focus on the development of the region's economic development model in the first year and the implementation and evaluation of programs of economic development in accordance with the model implemented in Year II. This research is a qualitative descriptive exploratory nature. The research location in the village Ngadas Poncokusumo District of Malang. The technique of collecting data using interviews, focus group discussions, observation and documentation. Data were analyzed using SWOT analysis and Analytical Hierarchy Process (AHP).